A MINI-FACTOR HEALTH AND SAFETY COMPLIANCE: A MULTIVARIATE FACTORIAL ANALYSIS - Zakari MUSTAPHA; Clinton AIGVABOA; Wellington THWALA (Journal of Construction Project Management and Innovation)
The construction industry employees all over the world experience serious injuries and deaths due to accidents in complex high-risk systems. These incidents have been attributed to conditions in which an employee is working or his actions that can result in human error or an unsafe action. Adherence to safety regulations features among Small and Medium-Sized Enterprises (SMEs) contractors’ in Ghana were confirmed through the use of a confirmatory factor analysis. Findings from the Structural Equation Modleing (SEM) analysis confirmed that the Rio coefficient and the Cronbach’s alpha coefficient on the internal consistency were over 0.70 criteria for acceptability. The influence of adherence to safety regulations features on the Health and Safety (H&S) compliance was found to be statistically significant. Hence, strong in predicting H&S compliance among SMEs contractors’. The paper makes a significance contribution towards SMEs contractors’ adherence to safety regulations. The paper provides a significant insight into how H&S compliance among SMEs contractors’ adherence to safety regulations could be improved.